The Role Of The Supervisory Council Notary Territory In Providing Legal Protection For A Notary Who Have Violated The Law Of The Deed Made - Kiki Andriani Samad; Amin Purnawan (Jurnal Akta, 2019)
The purpose of this study are 1) To clarify the role of the supervisory council notary territory in providing legal protection for a notary who have violated the law of the deed made. 2) To explain the regulatory obstacles and constraints assemblies notary territory in providing legal protection for a notary who have violated the law of the deed made.This research method is a normative juridical research is normative juridical method is the study of writing a good document that we study the norms and principles. Specification used in this study is a descriptive analysis, which is intended to give the data as accurately as possible about a situation or other symptoms. Based on the results of the study concluded thatLegal protection of the Notary, among others in the form of right of refusal, the obligation to reject and exclusive rights when summoned for questioning by investigators, prosecutors or judges, which is subject to approval of Honorary Council of Notaries of Regions as the provisions of Article 66 paragraph (1) of Act No. 2 2014 which has now been changed to Article 66 paragraph (1) of the Constitution of the Republic of Indonesia Number 2 Of 2014 concerning the Amendment to Act No. 30 of 2004 concerning Notary. Disagreement about the duties and responsibilities as a Council of Trustees Notary region between elements and bustle of every member of both government, notary, and academics to create obstacles during the examination and supervision of technical and administrative poorly in the recording report came from the community often happen, so data on the notary who has not and has been declared missing by the officials working at the Ministry of Justice and Human rights is also one member of the Supervisory Council of notaries, and only the remaining 1 data is still there on the notary who has been in the process by the Supervisory Council of notaries.Keywords: Regional Supervisory Council; Notary; Legal Protection; Notary; Law Violations; Deeds.